2006
DOI: 10.1002/gps.1523
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme (ACE) inhibitors modulate the rate of progression of amnestic mild cognitive impairment

Abstract: Older age, higher education, poor global cognitive performance, higher levels of plasma total homocysteine are independently associated with the progression of memory decline while the prescription of ACE Inhibitors is a protective factor for cognitive deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 43 publications
4
55
0
Order By: Relevance
“…Cumulative exposure of enalapril plus lisinopril and captopril (results not showed) compared with (A) those who were exposed to other antihypertensive drugs or (B) those with untreated hypertension a Model 1: partially adjusted models for age and gender b Model 2: fully adjusted models for age, gender, education, pack-years (0 for smokers and 1 for ever smokers), type 2 diabetes, coronary artery disease, serum creatinine level, and apolipoprotein B to apolipoprotein A1 ratio at baseline as well as history of stroke, history of hypertension, and other hypertension drug use at each wave evaluation. Patients with congestive heart failure exposed to ACE-Is were excluded from statistical evaluation A few small observational and case-control studies of individuals with MCI have suggested that ACE-Is slowed cognitive decline and reduced progression to AD (Hajjar et al 2005;He et al 2006;Rozzini et al 2006Rozzini et al , 2008. The present findings also support some suggestions from secondary analyses in two large stroke-prevention trials Syst-Eur (Forette et al 2002) and PROGRESS (Tzourio et al 2003), where a significant reduction in the incidence of dementia was found with antihypertensive therapies also including ACE-Is.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative exposure of enalapril plus lisinopril and captopril (results not showed) compared with (A) those who were exposed to other antihypertensive drugs or (B) those with untreated hypertension a Model 1: partially adjusted models for age and gender b Model 2: fully adjusted models for age, gender, education, pack-years (0 for smokers and 1 for ever smokers), type 2 diabetes, coronary artery disease, serum creatinine level, and apolipoprotein B to apolipoprotein A1 ratio at baseline as well as history of stroke, history of hypertension, and other hypertension drug use at each wave evaluation. Patients with congestive heart failure exposed to ACE-Is were excluded from statistical evaluation A few small observational and case-control studies of individuals with MCI have suggested that ACE-Is slowed cognitive decline and reduced progression to AD (Hajjar et al 2005;He et al 2006;Rozzini et al 2006Rozzini et al , 2008. The present findings also support some suggestions from secondary analyses in two large stroke-prevention trials Syst-Eur (Forette et al 2002) and PROGRESS (Tzourio et al 2003), where a significant reduction in the incidence of dementia was found with antihypertensive therapies also including ACE-Is.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, large-scale clinical trials of ACE-Is in AD and cognitive decline are lacking (Weiner et al 1992;Sudilovsky et al 1993;Louis et al 1999;Ohrui et al 2004b). In other small observational studies of individuals with MCI, ACE-Is slowed cognitive decline and reduced progression to AD (Hajjar et al 2005;He et al 2006;Rozzini et al 2006Rozzini et al , 2008. ACE-Is are described collectively as a "class" of drugs, but in reality, this classification is one of convenience based solely on their biological function which is the inhibition of ACE.…”
Section: Introductionmentioning
confidence: 99%
“…Previous non-randomized controlled studies on treatment of nephropathy by inhibiting the renin-angiotensin system (by angiotensin-converting enzyme inhibitors or angiotensin receptor blockers) showed protective effects on cognitive decline and reduced progression to dementia in patients with mild cognitive impairment [11,17] . However, in a population-based study the use of angiotensinconverting enzyme inhibitors was not associated with incident Alzheimer's disease [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure lowering has been shown to be effective in preventing stroke-related dementia, but the data on Alzheimer's disease are conflicting (24). The use of ACEIs was associated with reduced progression to dementia in patients with mild cognitive impairment (25) but not incident Alzheimer's disease in a population-based study (26).…”
Section: Predictors From Fds Recruitment (1993-1996)mentioning
confidence: 99%